PENGEMBANGAN MEDIA PEMBELAJARAN PINKAL BERBASIS SOAL CERITA PADA MATERI PERKALIAN KELAS IV SD - Hafifah, Dea Nur; Maulana, Maulana; Irawati, Riana (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
The learning process is identical to the use of learning media in the process of delivering learning material. The aim of this research is to find out how the development, effectiveness, and user response to pinkal learning media. Pinkal learning media is needed by teachers in the multiplication learning process, especially in solving multiplication story problems. The method used in this research is the R&D method. This development research uses the ADDIE research design proposed by Robert Maribe Branch. The subjects of this research were class IV students at SDN Pondok Bambu 06, East Jakarta. Data collection techniques use interviews, expert reviews, student response questionnaires, pretest-posttest, and documentation. Data was analyzed using quantitative and qualitative methods. The validation results from the two material experts obtained a total percentage of 100% with very feasible interpretation criteria. The validation results from the two media experts got a total percentage of 93% with very feasible interpretation criteria and the validation results from the two linguists got a total percentage of 99% with very feasible interpretation criteria. The results of the expert review show that pinkal learning media is very worthy of development. The effectiveness of the pretest and posttest results shows that learning with pinkal learning media has a significant effect on student learning outcomes. Student responses obtained a total percentage of 100% with very appropriate interpretation criteria. Based on the results of expert reviews, effectiveness and student responses, it can be concluded that pinkal learning media is effective for development.